Detection of equine arteritis virus in the semen of carrier stallions by using a sensitive nested PCR assay. - Gilbert, S A (1997)
A nested PCR, developed for the detection of equine arteritis virus (EAV) in semen, detected less than 2.5 PFU of EAV per ml of naturally infected seminal plasma. Based on results from testing 88 semen samples from 70 stallions, the sensitivity and specificity of the test were 100 and 97%, respectively.